EVALUASI SISTEM PENANGKAL PETIR DENGAN MENGGUNAKAN METODE SUDUT PROTEKSI PADA GEDUNG FAKULTAS KEDOKTERAN UNIVERSITAS BORNEO TARAKAN - Sugeng Riyanto; Dwi Risky Oktavia (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
Indonesia experiences a high frequency of thunderstorm days, which increases the vulnerability of multi-story buildings to lightning strikes. The Faculty of Medicine building at the University of Borneo Tarakan requires an evaluation of its lightning protection system to ensure safety and compliance. This study aims to analyze the effectiveness of the system using the Protection Angle Method and to measure the grounding resistance of the installed earthing system. The research applied a descriptive quantitative approach with a case study method. The analyzed parameters included building height, number of conductors, and soil resistivity, calculated based on SNI 03-7015-2004 and the General Regulation of Lightning Protection Installations (PUIPP). The results showed that with a building height of 25.3 meters, the system provided a protection radius of 25.3 meters and a protection efficiency of 0.91, classified as Protection Level III. However, several parts of the building were not optimally protected, requiring layout adjustments or additional air terminals. In conclusion, the lightning protection system is considered fairly effective, though improvements in grounding resistance and additional protection points are recommended to achieve full compliance with the standards..Indonesia merupakan salah satu negara dengan intensitas hari guruh tinggi, sehingga bangunan bertingkat berisiko besar terhadap sambaran petir. Gedung Fakultas Kedokteran Universitas Borneo Tarakan menjadi salah satu bangunan yang perlu dievaluasi sistem proteksi petirnya. Penelitian ini bertujuan menganalisis efektivitas sistem penangkal petir menggunakan metode sudut proteksi dan menilai resistansi tanah pada sistem pentanahan. Metode yang digunakan adalah kuantitatif deskriptif dengan pendekatan studi kasus, berdasarkan SNI 03-7015-2004 dan PUIPP. Hasil penelitian menunjukkan bahwa dengan tinggi bangunan 25,3 meter, sistem proteksi memiliki radius perlindungan 25,3 meter, luas area 11.673,5 m², dan efisiensi 0,91 (Proteksi Level III). Beberapa area belum terlindungi optimal dan nilai resistansi tanah perlu ditingkatkan agar sesuai standar. Secara keseluruhan, sistem proteksi petir dinilai cukup efektif, namun masih memerlukan perbaikan pada aspek pentanahan dan penambahan titik proteksi.